2008
DOI: 10.1002/eji.200737760
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 7‐mediated responses are defective in cord blood plasmacytoid dendritic cells

Abstract: Plasmacytoid dendritic cells (pDC) are specialized in massive production of type I interferons (IFN) upon viral infections. Activation of IFN regulatory factor (IRF)-7 is critically required for the synthesis of type I IFN in pDC. IRF-7 is highly expressed by resting pDC and translocates into the nucleus to initiate type I IFN transcription. In a previous work, we observed an impaired IFN-a production in enriched cord blood pDC following a TLR9 stimulation using CpG oligonucleotides. Herein, we show that highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 36 publications
(42 reference statements)
8
76
0
1
Order By: Relevance
“…The more severe manifestations seen in IRF3/7 Ϫ/Ϫ (and IFNAR Ϫ/Ϫ ) mice, hemorrhage, thrombocytopenia, and hypovolemic shock, have also been reported for severe CHIKV infections in human neonates and children (16,47), with such manifestations occasionally associated with mortality in neonates (16,37,45,47,57). Human neonates have defective innate antiviral responses, including defective IRF7-mediated responses (12,31). Hemorrhagic fever associated with CHIKV infections in children (13,24,45) and some adults (39,47) has also been reported.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The more severe manifestations seen in IRF3/7 Ϫ/Ϫ (and IFNAR Ϫ/Ϫ ) mice, hemorrhage, thrombocytopenia, and hypovolemic shock, have also been reported for severe CHIKV infections in human neonates and children (16,47), with such manifestations occasionally associated with mortality in neonates (16,37,45,47,57). Human neonates have defective innate antiviral responses, including defective IRF7-mediated responses (12,31). Hemorrhagic fever associated with CHIKV infections in children (13,24,45) and some adults (39,47) has also been reported.…”
Section: Discussionmentioning
confidence: 88%
“…Increased mortality was also seen after infection of IRF7 Ϫ/Ϫ or IRF3 Ϫ/Ϫ mice with the virulent West Nile virus strain (NY99), whereas infection with the naturally attenuated West Nile strain (Kunjin) was universally lethal only in IRF3/7 Ϫ/Ϫ doubleknockout mice (9). IRF7 has been shown to be important for optimum production of IFN-␣/␤ in murine embryonic fibroblasts (MEFs) after infection with a number of viruses (22) and is critical for IFN-␣/␤ production by plasmacytoid dendritic cells (12). IRF3 has been shown to be important for optimum IFN-␣/␤ production by nonhematopoietic and hematopoietic cells in response to certain virus infections (22), and IRF3-dependent apoptotic signaling can also contribute significantly to the host's protection from viral infection (4).…”
mentioning
confidence: 99%
“…It is well established that after antigen stimulation, both myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) from human cord blood express lower levels of MHC class II and the costimulatory molecules CD80 and CD86 than do adult peripheral blood DCs (31)(32)(33). Furthermore, neonatal mDCs and pDCs have a limited ability to produce IFN-α/β after pattern recognition receptor stimulation (34,35). In mammals, antigen presentation by these immature DCs results in the development of anergy or tolerance by the responding lymphocytes.…”
Section: Vaccinementioning
confidence: 99%
“…responses are known to be defective/underdeveloped (Levy 2007, Danis, George et al 2008 (Lee, Liu et al 2006, Pang, Cardosa et al 2007). …”
Section: Chikv Infection Of Ifnar -/-Mice Results In Rapid Lethal Hymentioning
confidence: 99%
“…The observed difference in mutation accrual may have implications chronic disease, whereby less mutated viral RNA is able to persist long term in the feet, while heavily mutated viral RNA in the lymph nodes accumulates too many mutations, and is thus unable to persist. (Levy 2007, Danis, George et al 2008, are more prone to development of DHF/DSS (Guzmán, Kouri et al 2002), and a study of children and young adults, found IRF7 transcriptional activity was associated with protection against development of DHS/DSS (Hoang, Lynn et al 2010). Furthermore, DHS/DSS patients have been found to have reduced type I IFN transcript levels (Simmons, Popper et al 2007).…”
Section: Summary Of Major Findingsmentioning
confidence: 99%